Molecular Cloning and Functional Analysis of a Na+-Insensitive K+ Transporter of Capsicum chinense Jacq - Ruiz-Lau, Nancy; Bojórquez-Quintal, Emanuel; Benito, Begoña; Echevarría-Machado, Ileana; Sánchez-Cach, Lucila A.; Medina-Lara, María de Fátima; Martínez-Estévez, Manuel (Frontiers in Plant Science, 2016)
High-affinity K+ (HAK) transporters are encoded by a large family of genes and are ubiquitous in the plant kingdom. These HAK-type transporters participate in low- and high-affinity potassium (K+) uptake and are crucial for the maintenance of K+ homeostasis under hostile conditions. In this study, the full-length cDNA of CcHAK1 gene was isolated from roots of the habanero pepper (Capsicum chinense). CcHAK1 expression was positively regulated by K+ starvation in roots and was not inhibited in the presence of NaCl. Phylogenetic analysis placed the CcHAK1 transporter in group I of the HAK K+ transporters, showing that it is closely related to Capsicum annuum CaHAK1 and Solanum lycopersicum LeHAK5. Characterization of the protein in a yeast mutant deficient in high-affinity K+ uptake (WΔ3) suggested that CcHAK1 function is associated with high-affinity K+ uptake, with Km and Vmax for Rb of 50 µM and 0.52 nmol mg-1 min-1, respectively. K+ uptake in yeast expressing the CcHAK1 transporter was inhibited by millimolar concentrations of the cations ammonium (NH4+) and cesium (Cs+) but not by sodium (Na+). The results presented in this study suggest that the CcHAK1 transporter may contribute to the maintenance of K+ homeostasis in root cells in C. chinense plants undergoing K+-deficiency and salt stress.